PENGARUH INSTITUTIONAL OWNERSHIP, AUDIT COMMITTEE DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - Candra, Cerry; Putri, Ariesta Tika Kinanti Pangestu Sulistyo (E-Jurnal Akuntansi TSM, 2024)
This study was used to determine the effect of the relationship between the variable independent and the variable dependent. Tax avoidance is the dependent variable, and the independent variables in this study are profitability, leverage, firm size, liquidity, capital intensity, audit committee, and institutional ownership. This study uses companies in the consumer non-cyclical and consumer cyclical sectors listed on the Indonesia Stock Exchange between 2020-2022. This research method uses purposive sampling. A total of 66 companies and 198 data were included among the samples that met the research sampling requirements. Multiple regression analysis was used in the statistical testing of this study. This study shows that there is a positive influence between tax avoidance and the variables of profitability and company size. While the variables of leverage, liquidity, capital intensity, audit committee, and institutional ownership have no effect on tax avoidance.